H2AX promotes replication fork degradation and chemosensitivity in BRCA-deficient tumours - Dibitetto, Diego; Liptay, Martin; Vivalda, Francesca; Dogan, Hülya; Gogola, Ewa; González Fernández, Martín; Duarte, Alexandra; Schmid, Jonas A.; Decollogny, Morgane; Francica, Paola; Przetocka, Sara; Durant, Stephen T.; et al. (Nature communications, 2024)
Histone H2AX plays a key role in DNA damage signalling in the surrounding regions of DNA double-strand breaks (DSBs). In response to DNA damage, H2AX becomes phosphorylated on serine residue 139 (known as γH2AX), resulting in the recruitment of the DNA repair effectors 53BP1 and BRCA1. Here, by studying resistance to poly(ADP-ribose) polymerase (PARP) inhibitors in BRCA1/2-deficient mammary tumours, we identify a function for γH2AX in orchestrating drug-induced replication fork degradation. Mechanistically, γH2AX-driven replication fork degradation is elicited by suppressing CtIP-mediated fork protection. As a result, H2AX loss restores replication fork stability and increases chemoresistance in BRCA1/2-deficient tumour cells without restoring homology-directed DNA repair, as highlighted by the lack of DNA damage-induced RAD51 foci. Furthermore, in the attempt to discover acquired genetic vulnerabilities, we find that ATM but not ATR inhibition overcomes PARP inhibitor (PARPi) resistance in H2AX-deficient tumours by interfering with CtIP-mediated fork protection. In summary, our results demonstrate a role for H2AX in replication fork biology in BRCA-deficient tumours and establish a function of H2AX separable from its classical role in DNA damage signalling and DSB repair. Histone H2AX has a known role in DNA damage repair but interestingly, its loss is associated with resistance to poly(ADP-ribose) polymerase (PARP) inhibition in BRCA-deficient tumours. Here, the authors identify a role of γH2AX in the degradation of replication forks and demonstrate that H2AX loss drives PARP inhibitor resistance via increased stressed fork stability in BRCA-deficient tumours.